ORGANIZING OF MANAGERIAL ACCOUNTING IN THE FORMING OF INFORMATION BASE OF BUILDING ENTERPRISES PROVIDING DEVELOPMENT - Pylypiv , N.I.; Motyl , V.M. (The actual problems of regional economy development, 2017)
This article explores the impact of organization of managerial accounting on formation of informational base on the local (level of the individual enterprise), regional, disciplinary and national levels in the context of providing stable economic development for building enterprises. Based on our findings, we built a cognitive map of such an influence, which shows itself through different spheres, such as: economic, ecological and social, and will enjoy informational requests of management for improving of effectiveness of management system of such kind of enterprises.